How to Draw the Brachial Plexus - Beth Krippendorf (Association of American Medical Colleges, 2005)
Abstract This brief, animated PowerPoint presentation guides anatomy students through the process of making a simple drawing of the brachial plexus. This mnemonic drawing has been presented informally to students in previous classes of Clinical Human Anatomy for first-year medical students at the Medical College of Wisconsin. It was so well received by students that in subsequent years, second-year students shared the mnemonic drawing with first-year students. Giving students the ability to draw the brachial plexus for themselves offers them a sense of ownership of the structure. Keeping the mnemonic drawing simple is a good first step on the path to learning the details (e.g., clinical signs of brachial plexus injury) of this nerve network.